Implementing X (Twitter) to Increase Student Vocabulary Mastery (Qualitative Descriptive Study) - Eka Puspita Anggraini; Haura Tuhfah Aziziya; Keisya Marezka Asyuranissa Jumantara Putri; Eisha Nur Ilmi Dessanda; Fahriany Fahriany; Didin Nuruddin Hidayat (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
This research describes whether X (Twitter) can increase students' vocabulary mastery of student's in the 5th semester of English Education Major at the State Islamic University of Syarif Hidayatullah Jakarta. An extensive vocabulary makes it easier for students to communicate their ideas and better understand what is being spoken and written. Although abundant studies on X (Twitter) are available in the literature, less attention has been given to the study of student's vocabulary. This study aims to shed light on using X (Twitter) to learn English slang for English Education students. This research uses qualitative descriptive methods using questionnaires to collect data. This study incorporated students from the fifth semester of the English Education Study Program at the State Islamic University of Syarif Hidayatullah Jakarta. Based on the data analysis, it is found that slang words on X (Twitter) help students maintain a variety of languages and provide a significant means for increasing a person's language abilities and vocabulary skills. So, it can be concluded that X (Twitter) can improve students' vocabulary mastery in the 5th semester of the English Education Department Faculty Tarbiyah State Islamic University Of  Syarif Hidayatullah Jakarta.